Potential mediators of the link between wealth index and anthropometric indices of under-five children in Ethiopia - Tesfaw, Lijalem Melie; Woya, Ashenafi Abate (Frontiers in Public Health, 2022)
Background: Malnutrition of under-five children has adverse effects on child health and development such as growth failure and muscle wasting. The household wealth index has a direct contribution to child malnutrition despite little attention being given to its indirect effect through other factors. This study aimed to identify the potential mediators of the link between wealth indexes to malnutrition. Methods: In this study, a cross-sectional study design was implemented based on the data obtained from the 2019 Ethiopia Mini Demographic and Health Survey (EMDHS) consists a total of 3918 under-five children. Mediation analysis of structural equation (SEM) was implemented to determine and estimate the effects of potential mediators of the link between wealth index and under-five children malnutrition. Results: Among 3918 under-five children involved in this study 51.4% were male and 20.2 % were from urban areas. The place of delivery of the majority of mothers (56.1%) was at home and the majority of children were from the poorest household (36.4%). The estimated effects of height-for-age of females were higher (1.31:95%CI=0.45, 0.200) indicates females children had a lower likelihood of stunting than males. As compared to children in an urban area, children from rural areas were more likely to be stunted (-0.269; 95%CI=-0.388,-0.135). The estimated total indirect effects of wealth index on stunting and underweight was 0.69 (95%=0.045, 0.094) and 0.036 (95%=0.013, 0.054) respectively, and significant (p-value<0.05). Conclusion: Environmental, maternal, biological, and behavioral factors were the potential mediators of the link between wealth index and anthropometric indices. Besides, the total effects of the household wealth index had a significant effect on stunting, underweight, and wasting in which children from a household with low economic status were more likely to be malnourished.